CULTURAL HOUSING AND FUNERAL PRACTICES AS SOCIAL TOOLS IN THE DEVELOPMENT OF RATIONALISM AND NON-VERBAL COMMUNICATION - Aalieva, Shirin; Satybaldieva, Rakhat; Erkinbekov, Kylychbek; Kubatbekov, Esenbek (Veredas do Direito, 2026)
The aim of this study is to identify the role of traditional housing and funeral practices of the Kyrgyz ethnic group as mechanisms for the development of rational thinking and non-verbal communication within the context of social organization and ethnic identity. The research is based on a qualitative analysis of philosophical, ethnographic, and cultural literature, as well as the interpretation of ritual elements of Kyrgyz traditional culture from the perspective of social work and interethnic interaction. The methods include comparative and hermeneutic approaches, semiotic analysis of housing structures (yurts), ritual gestures, and funeral customs, including the symbolism of space, color, and objects in traditional culture. The results show that the yurt and funeral rituals not only reflect a philosophical and cosmological worldview but also serve as forms of social regulation, support, communication, and the transmission of moral norms. The spatial structure of the yurt, the division by age, gender, and status, as well as symbolic actions during mourning, function as stable forms of non-verbal dialogue within the community. The conclusion emphasizes that cultural forms of dwelling and farewell play a key role in preserving ethnic cohesion, intergenerational dialogue, and strengthening social ties amid the transformation of traditional ways of life.